Is an online skin cancer toolkit an effective way to educate primary care physicians about skin cancer diagnosis and referral?. (27th April 2015) - Gulati, A.; Harwood, C.A.; Rolph, J.; Pottinger, E.; Mcgregor, J.M.; Goad, N.; Proby, C.M.
Abstract Background Skin disorders account for over 20% of GP consultations. Half of dermatology referrals to secondary care are for skin lesions, but only 12% of urgent skin cancer referrals are deemed appropriate. Suitably designed online learning resources may positively impact GP confidence in the recognition of skin cancer and improve patient outcomes. Objective This study evaluated the impact of a national, online, skin cancer recognition toolkit on GP confidence and knowledge in diagnosing skin cancers and referral behaviour to secondary care. Methods The toolkit, consisting of a referral decision aid, lesion recognition resource, clinical cases and a quiz, was launched in March 2012. Website usage statistics and online focus groups were used to assess the usability of the website and perceived changes in behaviour. The impact of the toolkit was assessed using national skin cancer referral data, cross‐sectional questionnaires and urgent skin cancer referral data to two NHS trusts. Results The toolkit was accessed by 20% of GPs in England from 20th March to 31st October 2012; spending a mean of over 5 minutes each, with over 33% return users. A survey revealed that the toolkit improved perceptions of skin cancer training and self‐reported knowledge about skin cancer referral pathways. Analysis of referral patterns did not identify an impact of the toolkit on number or appropriateness of urgent skin cancer referrals in the eight months following the launch of the website. Online focus groups confirmed the usefulness of the resource and suggested a positive influence on knowledge and referral behaviour. Conclusion The skin cancer toolkit is an accessible online learning resource for improving confidence with skin cancer referral amongst GPs. Although we were unable to identify any immediate changes in skin cancer diagnoses or appropriate referral behaviours, research is required to evaluate its longer term effects on outcomes.